Doing Knowledge Online Learning Model in Media Production-Based Subjects: High and Low Students’ Prior Knowledge Analysis - Rezi Ulya Fauziah; Mujahidah Auliya Ihsani; Jakfar Shodiq (APS-TPI, 2026)
Background: Technological innovations have transformed education by integrating digital tools and constructivist principles, fostering interactive and adaptive learning environments. Despite these advancements, challenges persist, particularly in hands-on subjects like media production, where traditional models often fail to bridge theory and practice.Aims: This study proposed the doing knowledge online learning model, designed to enhance media production education through active learning and social interaction. Methods: To evaluate the validity and effectiveness of the proposed model, the ADDIE Model was used as the instructional design framework, and a quasi-experimental design was employed for its implementation. A total of 80 students were assigned to two groups: the experimental group using the doing knowledge online learning model and the control group using the conventional learning model. Result: Results indicated that experts rated the model with a 93% agreement, classifying it as